MODEL RESEARCH OF THE ACIVE VIBROIZOLATION CABS MACHINE - Jerzy MARGIELEWICZ (Scientific Journal of Silesian University of Technology. Series Transport)
The study was carried out computer simulations of mechatronic model bridge crane, which is intended to theoretical evaluation of the possibility of eliminating the mechanical vibrations affecting the operator's cab driven machine. The model studies used fixed value control, the controlled variable is selected as the vertical displacement of the cab. Also included in the research model rheological model of the operator's body. We examined four overhead cranes with lifting capacity of 50T, which are classified in accordance with the directive of the European Union concerning the design of cranes, the four classes of cranes HC stiffness. The use of an active vibration isolation system in which distinguishes two negative feedback loops, very well eliminate mechanical vibration to the operator.